Effects of adding bulking agent, inorganic nutrient and microbial inocula on biopile treatment for oil-field drilling waste. (May 2016) - Ma, Jie; Yang, Yongqi; Dai, Xiaoli; Chen, Yetong; Deng, Hanmei; Zhou, Huijun; Guo, Shaohui; Yan, Guangxu
Abstract: Contamination from oil-field drilling waste is a worldwide environmental problem. This study investigated the performance of four bench-scale biopiles in treating drilling waste: 1) direct biopile (DW), 2) biopile plus oil-degrading microbial consortium (DW + M), 3) biopile plus microbial consortium and bulking agents (saw dust) (DW + M + BA), 4) biopile plus microbial consortium, bulking agents, and inorganic nutrients (Urea and K2 HPO4 ) (DW + M + BA + N). Ninety days of biopiling removed 41.0%, 44.0%, 55.7% and 87.4% of total petroleum hydrocarbon (TPH) in the pile "DW", "DW + M", "DW + M + BA", and "DW + M + BA + N" respectively. Addition of inorganic nutrient and bulking agents resulted in a 56.9% and 26.6% increase in TPH removal efficiency respectively. In contrast, inoculation of hydrocarbon-degrading microorganisms only slightly enhanced the contaminant removal (increased 7.3%). The biopile with stronger contaminant removal also had higher pile temperature and lower pile pH (e.g., in "DW + M + BA + N"). GC–MS analysis shows that biopiling significantly reduced the total number of detected contaminants and changed the chemical composition. Overall, this study shows that biopiling is an effective remediation technology for drilling waste. Adding inorganic nutrients and bulking agents can significantly improve biopile performance while addition of microbial inocula had minimal positive impacts on contaminant removal. Graphical abstract: Highlights: Biopiling is an effective remediation technology for oil-field drilling waste. Adding nutrient and bulking agent significantly enhanced biopiling performance. Inoculation of oil-degradation strains only slightly enhanced biopiling performance. Biopile with higher contaminant removal rate had lower pH and higher temperature. Biopiling significantly changed the chemical composition of contaminants.